The Routledge atlas of the Second World War - Gilbert, Martin 1936-2015 (Routledge, 2008)
Charts Second World War's political, military, economic and social history through 247 maps. This book covers major events from the German invasion of Poland in September 1939 to the defeat of Japan in August 1945, including the Blitz, the Fall of France, Pearl Harbor, and the naval Battles of the Atlantic